Visiting La Madre Patria: Heritage Pilgrimage Among Montreal Italians - Sanchini, Laura (Ethnologies, 2010)
This article focuses on visits to Italy undertaken by young Montreal Italians. I have divided these trips into three separate categories: the school trip, the extended stay, and the family visit. These trips allowed my informants to access Italy on three different levels. The school trip gave them the opportunity to experience the touristic elements of Italy, while the extended stay allowed them to understand the realities of living in Italy. The family visit gave them a chance to trace their family history and experience their parents' hometowns. These trips and the narratives that accompanied them have become identity markers for these Montreal Italians as well as a way for them to shape cultural awareness.